DEVELOPMENT AND IDENTIFICATION OF COMBINED PAIN ASPECTS IN LOW BACK PAIN: A REVIEW AND ANALYSIS - Friyan Maulana, Ilmi (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Lower back pain is a commonly occurring health issue and has a significant impact on the financial well-being of patients and their families. In the context of pathophysiology, pain can be classified into three main types: nociceptive pain, neuropathic pain, and central sensitization. Although about 85% of lower back pain cases lack a clear primary cause, the impact of this pain is palpable for patients. With the advancement of medical knowledge, the concept of Mixed Pain emerges as an entity where pain arises from a combination of several pathophysiological factors. However, the term